PENGARUH PEMBELAJARAN KOLABORATIF BERBASIS LESSON STUDY LEARNING COMMUNITY (LSLC) TERHADAP HASIL BELAJAR SISWA PADA POKOK BAHASAN PELUANG - Asih, Hastin Atas; Hobri, H; Oktavianingtyas, Ervin (Kadikma, 2018)
The purpose of this study was to determine whether or not there was an influence between Lesson Study Learning Community (LSLC) collaborative learning on student learning outcomes on opportunity topics in SMP Negeri 8 Jember.This research is an experimental study, using the form of True Experiment Design with Randomized Pre-test and Post-test Control Group Design research designs. The study population was all eighth grade students. The 3 class samples from 7 classes are homogeneous, the sample is divided into experimental class 1, experimental class 2, and control class. Data collection is done by documentation, tests and observations. Based on the results of F test data analysis on the Post-test value obtained Ftabel <Fhitung is 3.08 <11,673, then H0 is rejected. The results of the Post Hoc test showed that the experimental class 1 had a significant difference compared to the experimental class 2 and the control class. In the experimental class 1 students discussed to solve the problem, the interaction between students in the experimental class 1 happened well compared to the experimental class 2 and the control class, so that collaboration and student learning outcomes increased. Then it can be concluded that collaborative learning based on Lesson Study Learning Community (LSLC) influences student learning outcomes. Student learning outcomes in the experimental class 1 increased by 6.67%, this is higher than the experimental class 2 of 3.19 and the control class of 3.56. Keywords: Collaborative Learning, LSLC, Learning Outcomes